2010
DOI: 10.1111/j.1469-8986.2010.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, muscular and kinematic factors mediate performance under pressure

Abstract: It is well established that performance is influenced by pressure, but the underlying mechanisms of the pressure‐performance relationship are poorly understood. To address this important issue, the current experiment evaluated psychological, physiological, and kinematic factors as mediators of the pressure‐performance relationship. Psychological, physiological, and kinematic responses to three levels of competitive pressure were measured in 23 males and 35 females during a golf putting task. Pressure manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 48 publications
12
119
1
3
Order By: Relevance
“…Other authors have also considered HRV indices in relation to cognitive processes. Cooke and colleagues 22 observed how heart rate variability in LF increased under augmented pressure during golf putting. The authors attributed this result to the increase in respiratory volume under pressure.…”
Section: Psychophysiological Monitoring Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have also considered HRV indices in relation to cognitive processes. Cooke and colleagues 22 observed how heart rate variability in LF increased under augmented pressure during golf putting. The authors attributed this result to the increase in respiratory volume under pressure.…”
Section: Psychophysiological Monitoring Investigationsmentioning
confidence: 99%
“…This rhythm was also studied as a marker of resources allocation during motor programming 32 . Beta oscillation (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30),on the other hand, has a central position in the treatment of sensorimotor information and serves as a functional link between different brain regions such as the pre-motor, motor (M1), and somatosensory (S1) cortex, the supplementary motor area, and the cerebellum 31 . Beta oscillation could play the role of a motor "binding" linking the different commands related to a global gesture as suggested for sensory awareness 30 .…”
Section: Electroencephalography and Cortical Activity In Sportmentioning
confidence: 99%
“…For trials where the putt was holed, the experimenter recorded zero, and employed zero in the calculation of mean performance error (as Cooke, Kavussanu, McIntyre, & Ring, 2010).…”
Section: Performancementioning
confidence: 99%
“…The significance level for all analyses was set at a p-value of less than .05. Tests to analyze state anxiety, mental effort, MEP, and EMG were all one-tailed, because many previous studies of upper limb movement have found that these variables increase under pressure [6,7,[10][11][12][13]. The tests for other variables were two-tailed.…”
Section: Task Performancementioning
confidence: 99%
“…In terms of EMG amplitude, we hypothesized that increases in EMG amplitudes for both SOL and TA as well as co-contraction between the muscles would be observed under pressure. These predictions are based on previous upper limb findings that multiple corticospinal and EMG activities involving agonist, antagonist, synergist, and those muscles not directly involved are facilitated under pressure [6,7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%